1982
DOI: 10.1177/039139888200500611
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal Narcotic Tolerance: Preliminary Experience with Continuous Bupivicaine HCL Infusion via Implanted Infusion Device

Abstract: Spinal opiate receptor tolerance is the major limitation of continuous intraspinal narcotic analgesia delivered by implanted reservoir pump. Six intractable pain patients receiving continuous epidural morphine were given trials of low dose bupivicaine HCL in order to assess the effects on implanted reservoir function, analgesia, and safety. Daily infusion of 2.6-18.8 mg bupivicaine HCL had no consistent effect on flow rates. Subjectively, three patients had at least partial relief of pain while their intraspin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Ultimately, however, analgesic response diminished and bupivacaine was discontinued. Similar results have been reported by Hassenbusch and others [39,40]. Finally, in two patients with neuropathic pain resulting from arachnoiditis and sciatic neuropathy response to combination intraspinal morphine/clonidine (50 or 100 μg/day) was evaluated [41–43].…”
Section: Resultssupporting
confidence: 69%
“…Ultimately, however, analgesic response diminished and bupivacaine was discontinued. Similar results have been reported by Hassenbusch and others [39,40]. Finally, in two patients with neuropathic pain resulting from arachnoiditis and sciatic neuropathy response to combination intraspinal morphine/clonidine (50 or 100 μg/day) was evaluated [41–43].…”
Section: Resultssupporting
confidence: 69%
“…Since these early studies, numerous investigators have shown safety and efficacy with intrathecal administration of morphine for the treatment of chronic pain (10–13). Other drugs such as clonidine, hydromorphone, bupivacaine, and analgesic peptides have been used in addition to or as alternatives to morphine infusion (14–16). In the case of narcotic infusion for pain control, the importance of neither under‐ nor overdosing is obvious.…”
Section: Introductionmentioning
confidence: 99%